General ecology of coastal fish from the South Shetland Island and west Antarctic Peninsula areas - Barrera Oro, Esteban; Casaux, Ricardo Jorge
There is a lower diversity of Antarctic fish species on the continental shelves (139 spp) compared with other cold-water seas (> 350 spp in the North Atlantic). However, although the diversity of the notothenioids is limited compared with the large size of the ecosystem, there is no other fish group in the world with such a diversification and dominance in a continental shelf habitat (Eastman 1995). The role of fish as predators and prey in the Antarctic marine ecosystem is important for understanding energy flow from benthos and pelagic nekton, such as Antarctic krill, to predatory seals and penguins, and for understanding the potential for fisheries. This matter has been the object of several studies during the last three decades (reviewed in Kock 1992; Hureau 1994; Barrera-Oro 2002). Accordingly, this paper summarises published information from the long-term research program carried out by the Ichthyology Project of the Instituto Antártico Argentino in the period 1999-2006, focused on ecological aspects of fish in inshore sites of the South Shetland Islands and west Antarctic Peninsula. This research program allowed the development of studies about the ecology of fish (e.g. role in the food web, populational aspects, trophic position, age and growth, predator-prey interactions), as well as about the impact of the offshore commercial fishery/scientific programs on inshore fish of the area. Fil: Barrera Oro, Esteban. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina